Low-dose ketamine for supplement analgesia during minor day-case gynaecological surgery - Sondore, Antonina; Roga, Anita; Vanags, Indulis (Acta medica Lituanica, 2012)
Background. Preemptive low-dose Ketamine IV has been found to reduce anaesthetic drugs requirement, exert an excellent analgesia and may therefore be a useful component of general anaesthesia. Meanwhile, these data in literature are interpreted with caution. The aim of this study was to evaluate the efficacy and safety of preventive low-dose Ketamine as an adjuvant in the multimodal total intravenous anaesthesia (TIVA). Materials and methods. In this prospective study 40 women, ASA I-II, undergoing day-case minor gynaecological surgery, were enrolled. After premedication with Droperidol, Midazolam and Fentanyl in the study group (gr.), the patients (pts) received 0.2 mg/kg Ketamine (K gr., n = 20) and in the control gr. (C gr., n = 20) the patients received isotonic saline 30 sec before the induction of anaesthesia with Propofol. Anaesthesia was maintained with additional intermittent doses of Propofol, if required. The demand for a Propofol initial hypnotic dose and the requirement for additional intermittent doses, respiratory and cardiovascular reactions just after injection of drugs and during the perioperative period; times for response to verbal commands (early recovery) and for late recovery (physical capability), side-effects were registered perioperatively. Results. The results demonstrate that K gr. required significantly less Propofol, necessary for sleep (48.25 ± 12.69 mg vs. 101.50 ± 16.94 mg in C gr. which was by 47% more; t = 11.27, p =